CREATIVITY IS NOT ENOUGH: UNLOCKING ENTREPRENEURIAL READINESS THROUGH SELF-EFFICACY AND AUTHORITATIVE PARENTING - Miswanto Miswanto; Tiara Nur Anisah; Kartinah Kartinah (EKUITAS (Jurnal Ekonomi dan Keuangan), 2026)
This study addresses the critical "intention-action gap" in the global entrepreneurship landscape, specifically responding to the high unemployment rate among educated Indonesian youth. Grounded in Social Cognitive Theory, this research investigates the determinants of Entrepreneurial Readiness by integrating environmental factors (Authoritative Parenting) and cognitive traits (Entrepreneurial Alertness and Creativity), with Entrepreneurial Self-Efficacy proposed as a mediating mechanism. Adopting a quantitative cross-sectional design, data were collected from 250 Indonesian youths engaged in entrepreneurship education and analyzed using PLS-SEM. The results reveal that Authoritative Parenting and Entrepreneurial Alertness significantly and directly influence Entrepreneurial Readiness. Notably, Entrepreneurial Creativity does not have a direct effect but influences readiness through a complete mediation mechanism of Entrepreneurial Self-Efficacy. Furthermore, Self-Efficacy mediates the impact of alertness but fails to mediate the influence of parenting. Theoretically, this study resolves the creativity-readiness paradox by confirming self-efficacy as a "critical bridge" that transforms latent creative ideas into behavioral readiness. Practically, findings suggest that educators must shift from mere knowledge transfer to validating student creativity to build necessary confidence, while highlighting that supportive parenting serves as a fundamental incubator for entrepreneurial mental readiness. Furthermore, Self-Efficacy mediates the effect of alertness but does not mediate the effect of parenting. Theoretically, this study resolves the creativity-readiness paradox by confirming self-efficacy as a "critical bridge" that transforms latent creative ideas into behavioral readiness. In practice, the findings suggest that educators must shift from merely transferring knowledge to validating student creativity to build necessary confidence, while highlighting that supportive parenting serves as a fundamental incubator for entrepreneurial readiness.